MUSEUM YANG INSTAGRAMABLE: Tinjauan Desain Interior yang Menjadi Tempat Favorit untuk Berfoto pada Museum De Tjolomadoe, Karanganyar - Yemima Nathania Santoso; sidhi pramudito (Jurnal Arsitektur ZONASI, 2022)
Instagram is a social media application that is very popular in this digital era. every photo or video that has been uploaded by the owner can describe what the account owner feels or experiences. From the photo or video hat have been uploaded, sometimes it can also be known what an individual or community is interested in at a certain time, which is often called something "instagramable". One of the things that often receive the term "instagramable" is architectural design, especially the interior design of a building.. Currently, many buildings are designed or renovated (especially interior design) to attract public interest, one of which is a museum. The De Tjolomadoe Museum in Karanganyar is used as the object of research because there are good ratings in several electronic media. In addition, this museum is unique because it is designed with an adaptive reuse approach. This research is a qualitative research with a grounded theory approach. The data collected is visual data (photos) that have been recorded on the upload of the Instagram application with the hash tag de tjolomadoe. The analysis was carried out by describing the visual data using the theory of interior design elements, which can then be found keywords in each interior design element. The results show that the combination of the "old-new" interior design concept is an attraction for visitors or can be said to be an "instagramable" museum. At the De Tjolomadoe Museum, the picture of an “instagramable” museum can be seen through the combination of the interior design of the existing sugar factory (floor, ceiling elements, space attributes) packaged with new interior elements (in the form of the use of colors, materials, and space facilities). This “old-new” interior design concept, apart from providing an attraction for visitors to take pictures, can also be an educational medium that supports aspects of the functionality of a museum. The findings of this study are expected to be an alternative interior design concept that can be considered for designing museums in the future that can attract public interest to visit.